Search for the production of scalar bottom quarks in pp collisions at square root(s) = 1.96 TeV. - Aaltonen, T; Adelman, J; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; Artikov, A; et al. (2010)
We report on a search for direct scalar bottom quark (sbottom) pair production in pp collisions at square root(s) = 1.96 TeV, in events with large missing transverse energy and two jets of hadrons in the final state, where at least one of the jets is required to be identified as originating from a b quark. The study uses a collider detector at Fermilab Run II data sample corresponding to 2.65 fb(-1) of integrated luminosity. The data are in agreement with the standard model. In an R-parity conserving minimal supersymmetric scenario, and assuming that the sbottom decays exclusively into a bottom quark and a neutralino, 95% confidence-level upper limits on the sbottom pair production cross section of 0.1 pb are obtained. For neutralino masses below 70 GeV/c2, sbottom masses up to 230 GeV/c2 are excluded at 95% confidence level.